Assessment of Guidance and Counselling Needs for Entrepreneurial Success Among Small and Medium-Sized Enterprise Owners in Zamfara State, Nigeria - Apanpa Taibat Olaide; Bamidele Olawale Vincent; Attahiru Yahaya (Golden Ratio of Social Science and Education, 2026)
Small and Medium-sized Enterprises (SMEs) constitute the backbone of economic diversification and employment generation in developing economies, including Nigeria. Despite their strategic relevance, SME sustainability is challenged by limited access to comprehensive support services, particularly psychosocial and advisory interventions. This study investigated the guidance and counselling needs of SME owners across Zamfara State, Nigeria, with an emphasis on three major entrepreneurial hubs: Gusau, Talata Mafara, and Kaura Namoda Local Government Areas (LGAs). A descriptive survey research design was employed, targeting registered SME owners and operators across the state's fourteen LGAs. Based on data from the Zamfara State Ministry of Commerce, Industry, and Cooperative Services, there are 1,236 registered SMEs distributed across all 14 LGAs. Utilizing Yamane's (1967) formula with a 5% margin of error, a sample of 303 respondents was drawn through stratified random sampling to ensure a proportional representation across all local government areas (LGAs). Data were collected using a structured questionnaire with validated scales measuring demographics, entrepreneurial performance indicators, perceived counselling needs and barriers to accessing support services. The instrument demonstrated acceptable internal consistency (Cronbach's α = 0.81). Results, analyzed through descriptive statistics and multiple regression analysis, revealed a significant positive relationship between access to counselling services and business performance (F = 3,299) = 7.21, p < .01; Adjusted R² = 0.61). Specifically, 83% of respondents reported never accessing formal counselling services, while 91% expressed a strong need for strategic guidance in stress management, decision-making, and business planning. Entrepreneurs with access to mentorship demonstrated 23% higher productivity. The study concludes that entrepreneurial counselling frameworks should be institutionalized within local business development agencies across all 14 LGAs. The practical implications for policy formulation, theoretical advancement, and SME development programming are discussed.